PTU-165 Worldwide Epidemiological Evidence Supports A Common Factor Predisposing To Non-cardia Gastric Cancer And Protecting From Oesophageal Adenocarcinoma. (9th June 2014) - Derakhshan, MH; Brewster, DH; Going, JJ; Robertson, EV; Arnold, M; Forman, D; McColl, KE
Abstract : Introduction: During last three decades, global incidence of oesophageal adenocarcinoma has increased more rapidly than any other cancer. A concurrent reduction in the incidence of gastric cancer has been reported from some populations. We aimed to examine the geographical pattern of oesophageal adenocarcinoma versus gastric non-cardia cancer across the world where reliable cancer registry data were available. Methods: Data were abstracted from "Cancer Incidence in Five Continents" Volume 10. Oesophageal and gastric cancers were selected based on ICD-10 codes C15 and C16, respectively. Oesophageal adenocarcinomas were identified by ICD-O morphology codes. Datasets reporting >500 cases for total gastric cancer and >100 for total oesophageal cancer were selected. We examined correlation between age-standardised Incidence rates (ASR) of oesophageal adenocarcinoma and non-cardia gastric cancer using Spearman's non-parametric correlation coefficient (CC). We also allocated cardia cancers into oesophageal and non-cardia gastric adenocarcinoma categories based on gender ratio for oesophageal adenocarcinoma and non-cardia gastric cancer in each dataset. Results: Out of 424 datasets from 290 cancer registries, 206 datasets covering 40 countries met the selection criteria. There was a strong inverse correlation between oesophageal adenocarcinoma and gastric non-cardia cancer in males (CC= –0.768, p < 0.001) and females (CC = –0.705, p < 0.001). After dividing cardia cancer into two subtypes with potentially oesophageal or gastric origin and adding them to original oesophageal adenocarcinoma or gastric non-cardia groups, the inverse correlation remained strong in males (CC= –0.660, p < 0.001) and females (CC= –0.536, p < 0.001). Oesophageal adenocarcinoma only showed a rise when incidence of non-cardia gastric cancer fell below 9/100, 000 person-years for males and 4.5/100, 000 person-years for females. Conclusion: This cross-sectional study is consistent with a common underlying factor predisposing to non-cardia gastric cancer and protecting from oesophageal adenocarcinoma, such as H. pylori atrophic gastritis. If this is the case, then the incidence of non-cardia gastric cancer would need to fall to substantially lower levels than currently seen in Far Eastern populations before any rise in oesophageal adenocarcinoma would be apparent. Disclosure of Interest: None Declared.